A cross-cultural study of eating disordered behaviour in female university residence students - Geach, Michele Fiona (Rhodes University, Faculty of Humanities, Department of Psychology, 1996)
The compilation of information on the incidence of eating disorders in South African university residence women has been identified as an urgent matter by the National Eating Disorders Coordinating Committee (NEDCC). This study was undertaken to determine the degree of eating disordered behaviour across cultures in female university residence students from the University of Natal, Durban and Pietermaritzburg campuses, and the University of Durban Westville. The Eating Disorder Inventory (EDI) was completed by 39 black, 41 white, 6 Indian and 4 Coloured students. It was hypothesised that white women would show higher rates of disordered eating; that black women in more advanced years of study ie. those who are more acculturated, would show more disordered eating behaviour than first year black students; that black females would demonstrate higher Body Mass Index (BMI) scores than white students; and that a positive relationship would be found between Socio-economic status (SES) and disordered eating. The results of this study indicated that there was no significant difference in disordered eating among black and white female students. Degree of disordered eating did not increase with year of study. Although black students demonstrated significantly higher BMI scores than white students, there was no difference in body dissatisfaction scores. Furthermore there was no relationship found between SES and degree of disordered eating behaviour. An attempt is made to explain these results by exploring the role of acculturation to Western appearance standards.
Keywords: Eating disorders -- South Africa -- Cross-cultural studies; Women college students -- South Africa